1994
DOI: 10.1073/pnas.91.18.8690
|View full text |Cite
|
Sign up to set email alerts
|

Functional magnetic resonance imaging of human prefrontal cortex activation during a spatial working memory task.

Abstract: Hih-speed magnetic resonance (MR) imaging was used to detect activation in the human prefrontal cortex induced by a spatial working memory task modeled on those used to elucidate neuronal circuits in nonhuman primates. Subjects were required to judge whether the location occupied by the current stimulus had been occupied previously over a sequence of 14 or 15 stimuli presented in various locations. Control tasks were similar in all essential respects, except that the subject's task was to detect when one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
229
3
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 427 publications
(259 citation statements)
references
References 19 publications
24
229
3
3
Order By: Relevance
“…Half of the subjects showed either bilateral dPFC activation during both tasks or matching unilateral dPFC activation in both tasks, consistent with the prior findings of similar lateralization in object and spatial tasks. However, the other half of the subjects showed bilateral activation in one of the tasks (most often the verbal task) and unilateral activation in the other, which was somewhat more consistent with the McCarthy group's f indings (McCarthy et al, 1994;McCarthy et al, 1996). We note, however, that no subjects showed uniquely right hemi-sphere activation in one task and uniquely left hemisphere activation in the other.…”
Section: Human Researchsupporting
confidence: 52%
See 1 more Smart Citation
“…Half of the subjects showed either bilateral dPFC activation during both tasks or matching unilateral dPFC activation in both tasks, consistent with the prior findings of similar lateralization in object and spatial tasks. However, the other half of the subjects showed bilateral activation in one of the tasks (most often the verbal task) and unilateral activation in the other, which was somewhat more consistent with the McCarthy group's f indings (McCarthy et al, 1994;McCarthy et al, 1996). We note, however, that no subjects showed uniquely right hemi-sphere activation in one task and uniquely left hemisphere activation in the other.…”
Section: Human Researchsupporting
confidence: 52%
“…However, McCarthy and colleagues have found that dPFC activation varies between object and spatial WM tasks (McCarthy et al, 1994;McCarthy et al, 1996). 8 Here, when subjects monitored a stimulus stream for repetitions of objects, both hemispheres showed significant dPFC activation, with higher levels in the left hemisphere than in the right (but for the opposite result, see Callicott et al, 1999).…”
Section: Human Researchmentioning
confidence: 99%
“…These operations could be seen as emergent properties of the functional connections between parietal and frontal pre-motor and DLPF regions. Fronto-parietal functional loops are common to a wide range of cognitive operations where the active maintenance of information on line is necessary (Coull and Nobre, 1998;Jonides et al, 1998;Mccarthy et al, 1994). However, interestingly, the pattern of activation typically associated to generic mechanisms of temporal attention (i.e., attention to stimuli presented in different moment in time vs. in different spatial locations) tend to be left lateralised (Coull and Nobre, 1998), while attention to spatial positions or stimulus features is classically associated to bilateral activation (Corbetta and Shulman, 2002;Nobre, 2001;Wojciulik and Kanwisher, 1999).…”
Section: An A-modal Right Hemisphere Superiority For Approximate Numementioning
confidence: 99%
“…This association has been argued most extensively in the context of the P300, an event-related potential (ERP) elicited by infrequent events. Neuroimaging studies [Grasby et al, 1993;Jonides et al, 1993;Cohen et al, 1994;McCarthy et al, 1994;Casey et al, 1995;Smith et al, 1995;Kawashima et al, 1996;Casey et al, 1997] together with physiological studies in monkeys [Niki, 1974;Mishkin and Manning, 1978;Goldman-Rakic, 1987;Fuster, 1988;Yajeya and Fuster, 1988] have largely focused on the involvement of frontal regions in higher cognitive processes such as working memory and inhibitory control. These studies provide better spatial resolution than do electrophysiology studies and suggest that different regions within prefrontal cortex are associated with different types of processing.…”
Section: Introductionmentioning
confidence: 99%
“…These studies provide better spatial resolution than do electrophysiology studies and suggest that different regions within prefrontal cortex are associated with different types of processing. For example, dorsolateral prefrontal cortex has been implicated in working memory [Goldman-Rakic, 1987;Fuster, 1988;Cohen et al, 1994;McCarthy et al, 1994;Smith et al, 1995], while more ventral regions of prefrontal cortex have been implicated in the suppression of prepotent responses as in the go/no-go task [Kawashima et al, 1996;Casey et al, 1997;Konishi et al, 1999]. Few imaging studies have examined the effects of manipulating target probability on these presumed prefrontal functions.…”
Section: Introductionmentioning
confidence: 99%